Opposition: mod Elith Olesen: De frigjorte og trællefolket - Amerikansk-engelsk indflydelse på dansk kirkeliv omkring år 1900 (Frederiksberg 1996, 928 s.). (Let udvidet i forhold til disputatshandlingen 25.10.96). - Lyby, Thorkild C. (Kirkehistoriske Samlinger, 1997)
The article is practically identical with the contribution made by the author as an official critic at the public defence of Elith Olesen’s thesis on October 25, 1996. The thesis deals with the influence of the American-English Revival and Holiness Movement on Danish church life about 1900, especially on church life in Copenhagen and in the province of Thy. Apart from pointing out some minor errors, the article mainly concentrates on Olesen’s methodological approach, against which some criticism is levelled. Nevertheless, the main results of the book are accepted as valid, and consequently the conclusion is that the doctorate is well-earned.